2020
DOI: 10.1155/2020/3807234
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Activity of Leptadenia hastata (Asclepiadaceae) on Acetaminophen-Induced Toxicity in Mice: In Vivo Study and Characterization of Bioactive Compounds through Molecular Docking Approaches

Abstract: Background and Objectives. Leptadenia hastata is a liana from the family of Asclepiadaceae used in tropical Africa to treat diabetes mellitus. In this study, we investigated its hepatoprotective mechanisms on acetaminophen- (APAP-) induced toxicity through in vivo and in silico approaches. Materials and Methods. Various aqueous extracts were prepared from this plant and preadministered per os to albino mice 3 h before APAP administration, once daily for one week. Animals from the normal group were given only d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Using the wild-type strain, the acetaminophen induced in experimental albino rats shows significant elevation in levels of the serum marker enzymes, aspartate transaminase and alanine transaminase, and of lipid peroxides with decreased levels of antioxidant enzymes such as superoxide dismutase and catalase, showing its high harmful potential [ 45 ]. In addition, this protocol has also been widely used for analyzing the protective and curative effects of plant extracts, especially associated with pathologies of the digestive system [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the wild-type strain, the acetaminophen induced in experimental albino rats shows significant elevation in levels of the serum marker enzymes, aspartate transaminase and alanine transaminase, and of lipid peroxides with decreased levels of antioxidant enzymes such as superoxide dismutase and catalase, showing its high harmful potential [ 45 ]. In addition, this protocol has also been widely used for analyzing the protective and curative effects of plant extracts, especially associated with pathologies of the digestive system [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is rich in bioactive compounds, including quinine, scopoletin, silibinin, dihydroxycoumarin, lupeol, lutein, β-carotene, cynanforidin, and gagminin. [243][244][245] The treatment of lupeol (42 mmol/ear) on the ear of male albino mice induced with croton prevented edema by 80%. Further structural modifications on lupeol, including acetylation, palmitoylation, and hemisuccinate ester, resulted in 72%, 54%, and 90% reduction in edema.…”
Section: Complementary and Alternative Medicine: Potential Elixirs Fo...mentioning
confidence: 99%
“…Decne, a member of the Asclepiadaceae family widely distributed in Tropical Africa, is one of the herbal remedies used by traditional healers to treat DM. 11 , 24 Furthermore, several experimental studies have reported the anti-diabetic activity of L hastata . 7 , 11 , 17 Other reported pharmacological and biological potentials of different parts of L hastata include antimicrobial, antiandrogenic, anti-inflammatory, and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
“…7 , 11 , 17 Other reported pharmacological and biological potentials of different parts of L hastata include antimicrobial, antiandrogenic, anti-inflammatory, and antibacterial activities. 24 The anti-DM activity of medicinal plants is also anchored on active pharmaceutical phytoconstituents, including phytochemicals, vitamins, and minerals. 11 This study investigated the phytochemicals, vitamins, and minerals in L hastata and employed computational techniques to discover potential HPA antagonists, drug-likeness, pharmacokinetics properties, and safety profiles of compounds identified in ethanol extract of L hastata (EELH) using gas chromatography–mass spectrophotometer (GC-MS) and gas chromatography–flame ionization detector (GC-FID).…”
Section: Introductionmentioning
confidence: 99%